Incremental contribution of pollination and other ecosystem services to agricultural productivity: effects of service quantity and quality - Garibaldi, Lucas Alejandro (2016)
Fil: Garibaldi, Lucas A. Universidad Nacional de Río Negro. Instituto de Investigaciones en Recursos Naturales, Agroecología y Desarrollo Rural. Río Negro, Argentina.